I tried to use the series for $\sin \pi x$ and maybe find something related to $\zeta(3)$, but didn't work. I'm guessing this integral needs more than the little calculus that I know. \begin{equation} \int_0^1 \frac{x-x^2}{\sin \pi x} dx = \frac{7 \zeta(3)}{\pi^3}. \end{equation}

  • $\begingroup$ Laplace transforms, residue theory, and parameterizations come to mind, if you know any of those. $\endgroup$ – user217285 May 24 '18 at 3:55
  • $\begingroup$ @Nitin While the residue theorem, no doubt, can integrate that, the OP added the real-analysis tag, indicating they want only real methods of integrating said integral. i.e no contour integration of that sort $\endgroup$ – Frank W. May 24 '18 at 3:56
  • 2
    $\begingroup$ You can use integration by parts and a simple variable substitution to get$$I=-\frac 8{\pi^3}\int\limits_0^{\pi/2}dx\, x\log\cot x$$ $\endgroup$ – Frank W. May 24 '18 at 4:21

$\displaystyle f(a):=\int\limits_0^1 x e^{ax}dx = \frac{1+e^a(a-1)}{a^2}$

$\displaystyle g(a):=\int\limits_0^1 x^2 e^{ax}dx = \frac{-2+e^a(a^2-2a+2)}{a^3}$

$\displaystyle \int\limits_0^1 \frac{x^2-x}{\sin(\pi x)}dx = i2\int\limits_0^1\frac{x^2-x}{e^{i\pi x}-e^{-i\pi x}}dx = i2\sum\limits_{k=0}^\infty \int\limits_0^1 (x^2-x)e^{-i\pi x(2k+1)}dx $

$\displaystyle = i2\sum\limits_{k=0}^\infty (g(-i\pi(2k+1))-f(-i\pi(2k+1)))$

$\displaystyle = 2\sum\limits_{k=0}^\infty i\frac{-2+i\pi(2k+1) + e^{-i\pi(2k+1)}(2+i\pi(2k+1))}{(-i\pi(2k+1))^3} \enspace$ with $\enspace e^{-i\pi(2k+1)}=-1$

$\displaystyle = -8\sum\limits_{k=0}^\infty\frac{1}{(\pi(2k+1))^3}=-\frac{8}{\pi^3}(1-\frac{1}{2^3})\zeta(3)=-\frac{7\zeta(3)}{\pi^3}$

| cite | improve this answer | |

First, denote the integral below as $I$$$I=\int\limits_0^1dx\space\frac {x(1-x)}{\sin\pi x}$$and through integration by parts on $u=x-x^2$, then we have

$$\begin{align*}I & =-\frac 1{\pi}(x-x^2)\log\cot\left(\frac {\pi x}2\right)\,\Biggr\rvert_0^1+\frac 1{\pi}\int\limits_0^1dx\, (1-2x)\log\cot\left(\frac {\pi x}2\right)\\ & =\frac 1{\pi}\int\limits_0^1dx\,\log\cot\left(\frac {\pi x}2\right)-\frac 2{\pi}\int\limits_0^1dx\, x\log\cot\left(\frac {\pi x}2\right)\\ & =-\frac 8{\pi^3}\int\limits_0^{\pi/2}dx\, x\log\cot x\tag1\end{align*}$$

where equation ($1$) comes from making the substitution $x\mapsto\frac {\pi x}2$. The latter integral can be evaluated by splitting up the natural log into two separate integrals and using the Fourier series for $\log\sin x$ and $\log\cos x$, which I have included below

$$\begin{align*}\log\cos x & =\sum\limits_{k\geq1}(-1)^{k-1}\frac {\cos2kx}{k}-\log 2\tag2\\\log\sin x & =-\sum\limits_{k\geq1}\frac {\cos 2kx}k-\log 2\tag3\end{align*}$$

Expanding ($1$) gives

$$I=-\frac 8{\pi^3}\underbrace{\int\limits_0^{\pi/2}dx\, x\log\cos x}_{I_1}+\frac 8{\pi^3}\underbrace{\int\limits_0^{\pi/2}dx\, x\log\sin x}_{I_2}\tag4$$

Call the first and second integrals $I_1$ and $I_2$ respectively. Using ($2$) and ($3$) gives the following two identities

$$\begin{align*}I_1 & =\int\limits_0^{\pi/2}dx\,\left(\sum\limits_{k\geq1}\frac {(-1)^{k-1}\cos 2kx}k-x\log 2\right)\\ & =\sum\limits_{k\geq1}\frac {(-1)^{k-1}}k\left[\frac {\pi}{4k^2}\sin\pi k+\frac 1{4k^3}\cos\pi k-\frac 1{4k^2}\right]-\frac {\pi^2}8\log2\\ & =\frac 14\sum\limits_{k\geq1}\frac {(-1)^{k-1}}{k^3}\cos\pi k-\frac 14\sum\limits_{k\geq1}\frac {(-1)^{k-1}}{k^3}-\frac {\pi^2}8\log 2\\ & \color{blue}{=-\frac 14\zeta(3)-\frac 3{16}\zeta(3)-\frac {\pi^2}8\log 2}\tag5\end{align*}$$

As a side note, the infinite sum with $\sin\pi k$ vanishes because $\sin\pi k=0$ for $k\in\mathbb{Z}$. In a similar manner, $I_2$ can be integrated as follows

$$\begin{align*}I_2 & =-\int\limits_0^{\pi/2}dx\,\left(\sum\limits_{k\geq1}\frac {\cos 2kx}k+x\log 2\right)\\ & =-\sum\limits_{k\geq1}\frac 1k\left[\frac {\pi}{4k}\sin\pi k+\frac 1{4k^2}\cos\pi k-\frac 1{4k^2}\right]-\frac {\pi^2}8\log 2\\ & =-\frac 14\sum\limits_{k\geq1}\frac {\cos\pi k}{k^3}+\frac 14\sum\limits_{k\geq1}\frac 1{k^3}-\frac {\pi^2}8\log 2\\ & \color{red}{=\frac 14\zeta(3)+\frac 3{16}\zeta(3)-\frac {\pi^2}8\log 2}\tag6\end{align*}$$

Substituting the results for ($5$) and ($6$) into ($4$) leaves us with

$$\begin{align*}I & =-\frac 8{\pi^3}\left[\color{blue}{-\frac 14\zeta(3)-\frac 3{16}\zeta(3)}\color{red}{-\frac 14\zeta(3)-\frac 3{16}\zeta(3)}\right]\\ & =\frac 7{\pi^3}\zeta(3)\end{align*}$$

Multiply by $-1$ to get the integral under question

$$\int\limits_0^1dx\space\frac {x^2-x}{\sin\pi x}\color{brown}{=-\frac 7{\pi^3}\zeta(3)}$$

| cite | improve this answer | |
  • 3
    $\begingroup$ This is quite the answer, (+1+eps) $\endgroup$ – user217285 May 24 '18 at 6:37
  • 2
    $\begingroup$ @Nitin Thanks! This means a lot! $\endgroup$ – Frank W. May 24 '18 at 13:40

Probably not an answer.

For the antiderivative $$I=2 \pi^3\int \frac{x^2-x}{\sin (\pi x)}\, dx$$ a CAS give the ugly $$I=-i \pi (2 x-1) \left(4 \text{Li}_2\left(e^{i \pi x}\right)-\text{Li}_2\left(e^{2 i \pi x}\right)\right)+8 \text{Li}_3\left(e^{i \pi x}\right)-\text{Li}_3\left(e^{2 i \pi x}\right)-$$ $$4 \pi ^2 (x-1) x \tanh ^{-1}\left(e^{i \pi x}\right)$$ $$\lim_{x\to 1} \, I=-7 \zeta (3)+i\frac{ \pi ^3}{2} \qquad \text{and} \qquad \lim_{x\to 0} \, I=7 \zeta (3)+i\frac{ \pi ^3}{2}$$

What is interesting is that a rather good approximation could be obtained using a $[2,2]$ Padé approximant built at $x=\frac 12$ making $$\frac{x^2-x}{\sin (\pi x)}=\frac{-\frac 14+ a(x-\frac 12)^2 }{1+ b(x-\frac 12)^2 }$$ where $$a=-\frac{384-48 \pi ^2+\pi ^4}{48 \left(\pi ^2-8\right)} \qquad \text{and} \qquad b=-\frac{5 \pi ^4-48 \pi ^2}{12 \left(\pi ^2-8\right)}$$ making the definite integral easy to solve (leading to a value of $\approx -0.271415$ while the exact value is $\approx -0.271377$).

Still more amazing (at least to me), the approximation $$\sin(y) \simeq \frac{16 (\pi -y) y}{5 \pi ^2-4 (\pi -y) y}\qquad (0\leq y\leq\pi)$$ proposed by Mahabhaskariya of Bhaskara I, a seventh-century Indian mathematician would lead to $-\frac{13}{48} \approx -0.270833$ .

| cite | improve this answer | |
  • $\begingroup$ +1 for mention of Indian mathematician Mahabhaskariya. As always your insight into numerical analysis is very amazing. $\endgroup$ – Paramanand Singh May 25 '18 at 15:55
  • 1
    $\begingroup$ @ParamanandSingh. May I confess that it has been one of my big emotions, as a scientist, to "discover" this (given as a comment to one of my questions on MSE). From that day, I started looking at the works of Indian mathematicians and I am just fascinated. Cheers. $\endgroup$ – Claude Leibovici May 26 '18 at 2:53

Following Frank W.,

$\begin{align} J&=\int_0^1 \frac{x^2-x}{\sin(\pi x)}\,dx\\ &=\frac 8{\pi^3}\int\limits_0^{\pi/2}x\log\cot x \,dx\end{align}$

Perform the change of variable $y=\tan x$,

$\begin{align}J&=-\frac 8{\pi^3}\int_0^{\infty}\frac{\ln x\arctan x}{1+x^2} \,dx\\ &=-\frac 8{\pi^3}\int_0^{1}\frac{\ln x\arctan x}{1+x^2} \,dx-\frac 8{\pi^3}\int_1^{\infty}\frac{\ln x\arctan x}{1+x^2} \,dx \\\end{align}$

In the second integral perform the change of variable $y=\dfrac{1}{x}$,

$\begin{align}J&=-\frac 8{\pi^3}\int_0^{1}\frac{\ln x\arctan x}{1+x^2} \,dx+\frac 8{\pi^3}\int_0^{1}\frac{\ln x\arctan\left( \frac{1}{x}\right)}{1+x^2} \,dx\\ &=-\frac 8{\pi^3}\int_0^{1}\frac{\ln x\arctan x}{1+x^2} \,dx+\frac 8{\pi^3}\int_0^{1}\frac{\left(\frac{\pi}{2}-\arctan x\right)\ln x}{1+x^2} \,dx\\ &-\frac {16}{\pi^3}\int_0^{1}\frac{\ln x\arctan x}{1+x^2} \,dx-\frac{4}{\pi^2}\text{G} \end{align}$

$\text{G}$ is the Catalan constant.


$\displaystyle K=\int_0^{1}\frac{\ln x\arctan x}{1+x^2} \,dx$

Define for $x\in [0;1]$,

$\begin{align}R(x)&=\int_0^x\frac{\ln t}{1+t^2}\,dt\\ &=\int_0^1 \frac{x\ln(xt)}{1+t^2x^2}\,dt \end{align}$

Observe that, $\displaystyle R(0)=0,R(1)=-\text{G}$.

Perform integration by parts,

$\begin{align}K&=\Big[R(x)\arctan x\Big]_0^1-\int_0^1 \frac{R(x)}{1+x^2}\,dx\\ &=-\frac{\pi}{4}\text{G}-\int_0^1 \int_0^1 \frac{x\ln(xt)}{(1+t^2x^2)(1+x^2)}\,dt\,dx \\ &=-\frac{\pi}{4}\text{G}-\int_0^1 \int_0^1 \frac{x\ln t}{(1+t^2x^2)(1+x^2)}\,dt\,dx-\int_0^1 \int_0^1 \frac{x\ln x}{(1+t^2x^2)(1+x^2)}\,dt\,dx\\ &=-\frac{\pi}{4}\text{G}-\frac{1}{2}\int_0^1 \left[\frac{\ln t}{1-t^2}\times \ln\left(\frac{1+x^2}{1+t^2x^2}\right)\right]_{x=0}^{x=1}\,dt-\int_0^1 \Big[\frac{\arctan(tx)\ln x}{1+x^2}\Big]_{t=0}^{t=1} \,dx\\ &=-\frac{\pi}{4}\text{G}-\frac{1}{2}\int_0^1 \frac{\ln\left( \frac{2}{1+t^2}\right)\ln t}{1-t^2}\,dt-K \end{align}$


$\begin{align} K&=-\frac{\pi}{8}\text{G}-\frac{1}{4}\int_0^1 \frac{\ln\left( \frac{2}{1+t^2}\right)\ln t}{1-t^2}\,dt\\ &=-\frac{\pi}{8}\text{G}-\frac{\ln 2}{4}\int_0^1 \frac{\ln t}{1-t^2}\,dt+\frac{1}{4}\int_0^1 \frac{\ln(1+t^2)\ln t}{1-t^2}\,dt \end{align}$


$\displaystyle L=\int_0^1 \frac{\ln(1+t^2)\ln t}{1-t^2}\,dt$

For $x\in [0;1]$ define,

$\begin{align}S(x)&=\int_0^x\frac{\ln t}{1-t^2}\,dt\\ &=\int_0^1 \frac{x\ln(tx)}{1-t^2x^2}\,dt \end{align}$

Perform integration by parts,

$\begin{align}L&=\Big[S(x)\ln(1+x^2)\Big]_0^1 -\int_0^1 \int_0^1\frac{2x^2\ln(tx)}{(1+x^2)(1-t^2x^2)}\,dt\,dx\\ &=S(1)\ln 2-\int_0^1 \int_0^1 \frac{2x^2\ln t}{(1+x^2)(1-t^2x^2)}\,dt\,dx-\int_0^1 \int_0^1\frac{2x^2\ln x}{(1+x^2)(1-t^2x^2)}\,dt\,dx\\ &=S(1)\ln 2-\int_0^1 \left[-\frac{t\ln t}{1+t^2}\ln\left(\frac{1+tx}{1-tx}\right)+\frac{\ln t}{t}\ln\left(\frac{1+tx}{1-tx}\right)-\frac{2\arctan x \ln t}{1+t^2}\right]_{x=0}^{x=1}\,dt-\\ &\int_0^1 \left[\frac{x\ln x}{1+x^2}\ln\left(\frac{1+tx}{1-tx}\right)\right]_{t=0}^{t=1}\,dx\\ &=S(1)\ln 2-\int_0^1 \left[\frac{\ln t}{t}\ln\left(\frac{1+tx}{1-tx}\right)-\frac{2\arctan x \ln t}{1+t^2}\right]_{x=0}^{x=1}\,dt\\ &=S(1)\ln 2-\int_0^1 \frac{\ln t}{t}\ln\left(\frac{1+t}{1-t}\right)\,dt+\frac{\pi}{2}\int_0^1 \frac{\ln t}{1+t^2}\,dt\\ &=S(1)\ln 2-\int_0^1 \frac{\ln t}{t}\ln\left(\frac{1+t}{1-t}\right)\,dt-\frac{1}{2}\pi\text{G} \end{align}$


$\displaystyle M=\int_0^1 \frac{\ln t}{t}\ln\left(\frac{1+t}{1-t}\right)\,dt$

Perform integration by parts,

$\begin{align}M&=\Big[\frac{1}{2}\ln^2 t \ln\left(\frac{1+t}{1-t}\right)\Big]_0^1-\int_0^1 \frac{\ln^2 t}{1-t^2}\,dt\\ &=-\int_0^1 \frac{\ln^2 t}{1-t^2}\,dt\\ \end{align}$

Using Taylor expansion,

$\displaystyle M=-\frac{7}{4}\zeta(3)$


$\displaystyle L=S(1)\ln 2+\frac{7}{4}\zeta(3)-\frac{1}{2}\pi\text{G}$


$\begin{align}K&=-\frac{\pi}{8}\text{G}-\frac{\ln 2}{4}S(1) +\frac{1}{4}L\\ &=-\frac{\pi}{8}\text{G}-\frac{\ln 2}{4}S(1) +\frac{1}{4}\left(S(1)\ln 2+\frac{7}{4}\zeta(3)-\frac{1}{2}\pi\text{G}\right)\\ &=\frac{7}{16}\zeta(3)-\frac{1}{4}\pi\text{G} \end{align}$


$\begin{align}J&=-\frac {16}{\pi^3}K-\frac{4}{\pi^2}\text{G}\\ &=-\frac {16}{\pi^3}\left(\frac{7}{16}\zeta(3)-\frac{1}{4}\pi\text{G}\right)-\frac{4}{\pi^2}\text{G}\\ &=\boxed{-\frac{7\zeta(3)}{\pi^3}} \end{align}$

| cite | improve this answer | |

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

$\ds{\int_{0}^{1}{x - x^{2} \over \sin\pars{\pi x}} \,\dd x = {7\zeta\pars{3} \over \pi^{3}}:\ {\LARGE ?}}$.

\begin{align} &\bbox[10px,#ffd]{\int_{0}^{1}{x - x^{2} \over \sin\pars{\pi x}}\,\dd x} \,\,\,\stackrel{x\ \mapsto\ x + 1/2}{=}\,\,\, \int_{-1/2}^{1/2}{1/4 - x^{2} \over \cos\pars{\pi x}}\,\dd x \\[5mm] = &\ {1 \over 2}\int_{0}^{1/2}{1 - 4x^{2} \over \cos\pars{\pi x}}\,\dd x \,\,\,\stackrel{\pi x\ \mapsto\ x}{=}\,\,\, {1 \over 2\pi^{3}}\int_{0}^{\pi/2}{\pi^{2} - 4x^{2} \over \cos\pars{x}}\,\dd x \\[5mm] = &\ \left. {1 \over 2\pi^{3}}\Re\int_{x\ =\ 0}^{x\ =\ \pi/2}{\pi^{2} - 4\bracks{-\ic\ln\pars{z}}^{2} \over \pars{z + 1/z}/2}\,{\dd z \over \ic z} \,\right\vert_{\ z\ =\ \exp\pars{\ic x}} \\[5mm] = &\ \left. {1 \over \pi^{3}}\,\Im\int_{x\ =\ 0}^{x\ =\ \pi/2}{\pi^{2} + 4\ln^{2}\pars{z} \over 1 + z^{2}}\,\dd z\,\right\vert_{\ z\ =\ \exp\pars{\ic x}} \\[5mm] = &\ -\,{1 \over \pi^{3}}\,\Im\int_{1}^{0}{\pi^{2} + 4\bracks{\ln\pars{y} + \ic\pi/2}^{\, 2} \over 1 + \pars{\ic y}^{2}}\,\ic\,\dd y \\[5mm] = &\ {4 \over \pi^{3}}\ \underbrace{\int_{0}^{1} {\ln^{2}\pars{y} \over 1 - y^{2}}\,\dd y} _{\ds{7\zeta\pars{3} \over 4}} = \bbx{7\zeta\pars{3} \over \pi^{3}} \approx 0.2714 \end{align}

| cite | improve this answer | |
  • $\begingroup$ Why is the last identity true? $\endgroup$ – Maximilian Janisch Dec 22 '19 at 1:11

Basically The Same As @FrankW.

First, a warmup integral.

Let $$S(x)=\int\frac{dx}{\sin\pi x}\overset{t=\pi x}=\frac1\pi \int\frac{dt}{\sin t}.$$ The sub $u=\tan(t/2)$ provides $$S(x)=\frac1\pi\int\frac{1}{\frac{2u}{1+u^2}}\frac{2du}{1+u^2}=\frac1\pi\ln\tan\frac{\pi x}{2}\ .$$ So we have that the integral in question is $$I=\frac1\pi\int_0^1(x-x^2)\left(\ln\tan\tfrac{\pi x}{2}\right)'\ dx.$$ Thus $$\begin{align} \pi I&=\underbrace{(x-x^2)\ln\tan\tfrac{\pi x}{2}\bigg |_0^1}_{=0}+\int_0^1(2x-1)\ln\tan\tfrac{\pi x}{2}\ dx\\ &=2\int_0^1 x\ln\tan\tfrac{\pi x}{2}\ dx-\underbrace{\int_0^1\ln\tan\tfrac{\pi x}{2}\ dx}_{=0}\\ &=\frac2{\pi^2}\int_0^\pi x\ln\tan\tfrac{x}{2}\ dx\ . \end{align}$$ Then recall the definition of the Clausen function of order $2$: $$\mathrm{Cl}_2(x)=-\int_0^x \ln\left|2\sin\tfrac{t}{2}\right|\ dt.$$ Then using the Fourier series given by @FrankW. one can show that $$\mathrm{Cl}_2(x)=\sum_{k\ge1}\frac{\sin kx}{k^2}.$$ So we have $$\begin{align} \int_0^x \ln\tan\tfrac{t}{2}\ dt&=\int_0^x \ln\left(2\sin\tfrac{t}{2}\right)\ dt-\int_0^x \ln\left(2\cos\tfrac{t}{2}\right)\ dt\\ &=-\mathrm{Cl}_2(x)-\int_0^x \ln\left(2\cos\tfrac{t}{2}\right)\ dt\\ &=-\mathrm{Cl}_2(x)-\mathrm{Cl}_2(\pi-x). \end{align}$$ Integration by parts again: $$\begin{align} \frac{\pi^3}{2}I&=\left[-x(\mathrm{Cl}_2(x)+\mathrm{Cl}_2(\pi-x))\right]_0^\pi+\int_0^\pi\mathrm{Cl}_2(x)dx+\int_0^\pi \mathrm{Cl}_2(\pi-x)dx\\ &=\int_0^\pi\mathrm{Cl}_2(x)dx+\int_0^\pi \mathrm{Cl}_2(\pi-x)dx\\ &=2\int_0^\pi\mathrm{Cl}_2(x)dx. \end{align}$$ Next, we recall the definition of the $n$-th order Clausen function: $$\mathrm{Cl}_n(x)=\sum_{k\ge1}\frac{p_n(kx)}{k^n}$$ where $$p_n(x)=\Bigg\{{{\cos x\qquad n \text{ odd}}\atop{\sin x\qquad n\text{ even}}}$$ so that $$\int \mathrm{Cl}_n(x)dx=(-1)^{n+1}\mathrm{Cl}_{n+1}(x).$$ So at long last, $$I=\frac4{\pi^3}\left(\mathrm{Cl}_3(0)-\mathrm{Cl}_3(\pi)\right).$$ Since $p_3(0)=1$ and $p_3(\pi k)=(-1)^k$ we have that $$I=\frac{4}{\pi^3}\sum_{k\ge1}\frac1{k^3}[1-(-1)^k]=\frac{7\zeta(3)}{\pi^3}.$$

| cite | improve this answer | |

I will present an evaluation that makes use of the following two Euler sums:

$$\sum_{n = 1}^\infty \frac{(-1)^n H_n}{n^2} = -\frac{5}{8} \zeta (3) \qquad \text{and} \qquad \sum_{n = 1}^\infty \frac{(-1)^n H_{2n}}{n^2} = \frac{23}{16} \zeta (3) - \pi \mathbf{G}.$$

Here $\mathbf{G}$ is Catalan's constant. For a proof of the first, see either here or Eq. (646) in this link. For a proof of the second, see Eq. (659) in this link.

Writing $$I = \int_0^1 \frac{x(1 - x)}{\sin (\pi x)} \, dx,$$ following on from what others have already recognised, we can write the integral as $$I = -\frac{8}{\pi^3} \int_0^{\frac{\pi}{2}} x \ln (\cot x) \, dx = \frac{8}{\pi^3} \int_0^{\frac{\pi}{2}} x \ln (\tan x) \, dx.$$ Enforcing a substitution of $x \mapsto \arctan x$ gives \begin{align} I &= \frac{8}{\pi^3} \int_0^\infty \frac{\ln x \arctan x}{1 + x^2} \, dx\\ &= \frac{8}{\pi^3} \int_0^1 \frac{\ln x \arctan x}{1 + x^2} \, dx + \frac{8}{\pi^3} \int_1^\infty \frac{\ln x \arctan x}{1 + x^2} \, dx\\ &= \frac{8}{\pi^3} \int_0^1 \frac{\ln x \arctan x}{1 + x^2} \, dx - \frac{8}{\pi^3} \int_0^1 \frac{\ln x \left (\frac{\pi}{2} - \arctan x \right )}{1 + x^2} \, dx\\ &= \frac{16}{\pi^3} \int_0^1 \frac{\ln x \arctan x}{1 + x^2} \, dx - \frac{4}{\pi^2} \int_1^\infty \frac{\ln x}{1 + x^2} \, dx\\ &= \frac{16}{\pi^3} I_1 - \frac{4}{\pi^2} I_2.\tag1 \end{align}

For the first integral $I_1$

Applying the Cauchy product to the product between the Macluarin series for $\arctan x$ and $\frac{1}{1 + x^2}$, one readily finds $$\frac{\arctan x}{1 + x^2} = \sum_{n = 0}^\infty (-1)^n \left (H_{2n + 1} - \frac{1}{2} H_n \right ) x^{2n + 1}, \qquad |x| < 1.$$ Here $H_n$ is the $n$th Harmonic number.

Thus \begin{align} I_1 &= \sum_{n = 0}^\infty (-1)^n \left (H_{2n + 1} - \frac{1}{2} H_n \right ) \int_0^1 x^{2n + 1} \, dx\\ &= \sum_{n = 0}^\infty (-1)^n \left (H_{2n + 1} - \frac{1}{2} H_n \right ) \frac{d}{ds} \left [\int_0^1 x^{2n + s + 1} \, dx \right ]_{s = 0}\\ &= -\sum_{n = 0}^\infty (-1)^n \left (H_{2n + 1} - \frac{1}{2} H_n \right ) \frac{1}{(2n + 2)^2}\\ &= -\frac{1}{4} \underbrace{\sum_{n = 0}^\infty \frac{(-1)^n H_{2n + 1}}{(n + 1)^2}}_{n \, \mapsto \, n -1} + \frac{1}{8} \underbrace{\sum_{n = 0}^\infty \frac{(-1)^{n} H_n}{(n + 1)^2}}_{n \, \mapsto \, n - 1}\\ &= -\frac{1}{4} \sum_{n = 1}^\infty \frac{(-1)^{n-1} H_{2n - 1}}{n^2} + \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^{n-1} H_{n-1}}{n^2}\\ &= \frac{1}{4} \sum_{n = 1}^\infty \frac{(-1)^n}{n^2} \left (H_{2n} - \frac{1}{2n} \right ) - \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^n}{n^2} \left (H_{n} - \frac{1}{n} \right )\\ &= \frac{1}{4} \sum_{n = 1}^\infty \frac{(-1)^n H_{2n}}{n^2} - \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^n}{n^3} - \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^n H_n}{n^2} + \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^n}{n^3}\\ &= \frac{1}{4} \sum_{n = 1}^\infty \frac{(-1)^n H_{2n}}{n^2} - \frac{1}{8} \sum_{n = 1}^\infty \frac{(-1)^n H_n}{n^2}\\ &= \frac{1}{4} \left (\frac{23}{16} \zeta (3) - \pi \mathbf{G} \right ) - \frac{1}{8} \left (-\frac{5}{8} \zeta (3) \right )\\ &= \frac{7}{16} \zeta (3) - \frac{\pi}{4} \mathbf{G}.\tag2 \end{align}

For the second integral $I_2$

\begin{align} I_2 &= \int_0^1 \frac{\ln x}{1 + x^2} \, dx\\ &= \sum_{n = 0}^\infty (-1)^n x^{2n} \ln x \, dx\\ &= \sum_{n = 0}^\infty (-1)^n \frac{d}{ds} \left [ \int_0^1 x^{2n + s} \right ]_{s = 0}\\ &= \sum_{n = 0}^\infty (-1)^n \frac{d}{ds} \left [\frac{1}{2n + s + 1} \right ]_{s = 0}\\ &= -\sum_{n = 0}^\infty \frac{(-1)^n}{(2n + 1)^2}\\ &= - \mathbf{G}\tag3 \end{align}

Main integral

On returning to the main integral, substituting (2) and (3) into (1) one sees that $$I = \frac{16}{\pi^3} \left (\frac{7}{16} \zeta (3) - \frac{\pi \mathbf{G}}{4} \right ) + \frac{4 \mathbf{G}}{\pi^2},$$ or $$\int_0^1 \frac{x(1 - x)}{\sin (\pi x)} \, dx = \frac{7}{\pi^3} \zeta (3),$$ as required.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.